Equilibrium, thermodynamic, and kinetic of Cr(VI) adsorption using a modified and unmodified bentonite clay - D.J.L. Guerra; I. Mello; L.R. Freitas; R. Resende; R.A.R. Silva (International Journal of Mining Science and Technology, 2014)
The capacities of natural and modified Brazilian bentonite samples as adsorbents to remove hexavalent metal chromium were investigated under several conditions in batch and column methods. The raw material, Ca-bentonite, was modified by anchorament of 3-aminopropyltrietoxisilane (APS) and 3,2-aminoethylaminopropyltrimetoxisilane (AEAPS) in the surface of bentonite sample. This type of new occurrence of bentonite is suitable as a raw material for adsorption process. Adsorption behavior of three bentonite types was strongly depending on pH of adsorbate solution, contact time adsorbent/adsorbate, and initial concentration of Cr(VI). The results were confirmed by column method and reveals that the adsorption process of materials accorded by the Redlich-Peterson, Sips, Dubinin-Radushkevich, and Langmuir isotherm models. The exothermic enthalpic values reflected a favorable energetic process for chromium ions anchored in the material surfaces. The negative Gibbs free energy results supported the spontaneity of three adsorption reactions with Cr(VI) ions. Keywords: Bentonite, Organo-bentonite, Chromium, Equilibrium, Kinetic, Adsorption